Penguatan Branding Produk dan Promosi Digital Berbasis Media Sosial bagi Siswa MA Al-Amin - Ilman Ilman; Rexy Kurniawan; Pahruroji Pahruroji; Jumriah Oktawisanti; Siti Nurul Hidayah; Melinne Maldini Rosady (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
This article discusses a community service activity conducted at MA Al-Amin, Jayanti, Tangerang Regency. The initial condition showed that students were already familiar with social media, but their use was still dominated by entertainment, personal communication, and content consumption rather than productive activities such as product promotion and business communication. The program was designed to strengthen students' understanding of product branding, visual identity, simple smartphone-based product photography, social media promotion strategies, cyber safety, and digital business ethics. The activity was carried out offline on April 16, 2026, involving 25 students. The learning process combined short presentations, contextual examples, interactive discussions, question-and-answer sessions, and simple evaluation through pre-test and post-test. The training materials covered personal data protection, brand identity, visual consistency, promotional content using the AIDA approach, the use of Instagram, TikTok, and WhatsApp Business, and ethical communication in digital promotion. The evaluation results indicated an improvement in participants' understanding after the training. Students became more aware that social media can be used not only for entertainment, but also for learning, creativity, product introduction, and early entrepreneurship. This activity is expected to encourage students to use digital platforms more creatively, productively, safely, and responsibly.